2006
DOI: 10.1242/dev.02340
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flowering time byArabidopsis MSI1

Abstract: The transition to flowering is tightly controlled by endogenous programs and environmental signals. We found that MSI1 is a novel flowering-time gene in Arabidopsis. Both partially complemented msi1 mutants and MSI1 antisense plants were late flowering, whereas ectopic expression of MSI1 accelerated flowering. Physiological experiments revealed that MSI1 is similar to genes from the autonomous promotion of flowering pathway. Expression of most known flowering-time genes did not depend on MSI1, but the inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 66 publications
6
127
0
2
Order By: Relevance
“…Similar to Trx, Set1 functions in a large protein complex, COMPASS (Complex Proteins Associated with Set1), in mediating histone methylation [71,72]. In Arabidopsis, it has been demonstrated that H3K4 methylation is associated with a permissive state of gene expression during plant development [73,74]. ATX1 (subgroup III-1; Table 1) was the first protein confirmed to have H3K4 methyltransferase activity in plants and it is involved in floral development through activating flower homeotic genes [75,76].…”
Section: Class Iii: the Trithorax Homologs And Related Proteins (H3k4)mentioning
confidence: 99%
“…Similar to Trx, Set1 functions in a large protein complex, COMPASS (Complex Proteins Associated with Set1), in mediating histone methylation [71,72]. In Arabidopsis, it has been demonstrated that H3K4 methylation is associated with a permissive state of gene expression during plant development [73,74]. ATX1 (subgroup III-1; Table 1) was the first protein confirmed to have H3K4 methyltransferase activity in plants and it is involved in floral development through activating flower homeotic genes [75,76].…”
Section: Class Iii: the Trithorax Homologs And Related Proteins (H3k4)mentioning
confidence: 99%
“…For a suppressor screen, seeds of the late-flowering msi1-tap1 transgenic line (Bouveret et al, 2006) were mutagenized with ethyl methane sulfonate (EMS; Exner et al, 2009). Flowering time was scored under LD photoperiods for 1,045 M2 families.…”
Section: Isolation Of a New Cry1 Allelementioning
confidence: 99%
“…The line msi1-tap1 (accession Col) has been described before (Bouveret et al, 2006). The EMS allele cry1-L407F (accession Col) was isolated from a mutant screen (this study).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Both EMF-PRC2 and VRN-PRC2 complexes can together control the development of the sporophyte and have a major role in ensuring differentiation and repressing stem cell genes (Bemer and Grossniklaus 2012). The loss of Arabidopsis MSI1 function results in numerous disorders in the vegetative and embryogenic development, leads to defects in shoot apical meristems, floral meristems, primordia and embryo abortion at different developmental stages Köhler et al 2003;Bouveret et al 2006;Schönrock et al 2006;Steinbach and Hennig 2014). In msi mutant plants displayed defects in cell division on early stages of embryogenesis and over-proliferation with deficiency in differentiation of embryos (Köhler et al 2003;Guitton et al 2004), indicating an important role of MSI1 in the zygotic embryo development control.…”
Section: Introductionmentioning
confidence: 99%